Fighting for a living : a comparative history of military labour 1500-2000 - Zürcher, Erik Jan (Work around the globe, 2013)
"Fighting for a living investigates the circumstances that have produced starkly different systems of recruiting and employing soldiers in different parts of the globe, over the last 500 years. Offering a wide range of case studies taken from Europe, America, the Middle East and Asia, this volume is not military history in the traditional sense, but looks at military service and warfare as forms of labour, and at soldiers as workers. Military employment offers excellent opportunities for international comparison: armies as a form of organized violence are ubiquitous, and soldiers, in one form or another, are always part of the picture, in any period and in every region. Fighting for a living is the first study to undertake a systematic comparative analysis of military labour. It therefore will be of interest to both labour historians and military historians, as well as to sociologists, political scientists, and other social scientists"--Page 4 of cover